COMPOSITE MATERIALS FOR WEAR-RESISTANT COATINGS OF AGRICULTURAL MACHINERY PARTS - Shamrai, Vitaliy; Mikosianchyk, Oksana; Lopata, Larysa; Golembiyevskyy, Grygoriy; Horb, Yehor (Problems of Friction and Wear, 2023)
An analysis of the compatibility of the matrix and fillers as components for wear-resistant composite materials was carried out. The study demonstrated that using of composite ceramic-metallic materials increase wear resistance of working parts of agricultural machinery. The study analyzed the effectiveness of the use of composite materials with dispersed particles of refractory phases, ferroalloys, self-fluxing alloys based on nickel and iron for strengthening parts of agricultural machinery that operates in conditions dominated by abrasive and corrosive-mechanical wear. The study determined that the suitable materials for applying wear-resistant composite coatings to parts that work under conditions of abrasive wear combined with strong impacts are СM, where fillers are dispersed particles of refractory phases - oxides and carbides, and СM containing increased nickel content. The study also analyzed the expediency of using component materials for the creation of composite coatings, such as matrix - PG-С1, PG1, and reinforcing components - carbon ferrochrome FX-800, chromium carbide. The study considered the structure of powder composite materials, the structure of clad and conglomerate particles, and the structure of heterodisperse and homodisperse conglomerate particles. Furthermore, the study considered the effectiveness of the use of self-fluxing alloys as a multicomponent heterogeneous system based on Ni, Co, Fe, containing a soft matrix and solid dispersed inclusions of carbide, boride, and silicide. The study determined that use of self-fluxing iron-based alloys increases a wear resistance, hardness and other properties of working parts of agricultural machines. The study defined the role of the dispersed particles and matrix in wear-resistant composite coatings. The compatibility criteria for the selection of components of composite materials are given. The main compatibility criteria include a coefficient of thermal expansion close to the base material; no adverse effect on the properties of the base; diffusive inertness to the base; sufficient adhesion; a set of necessary operational characteristics; economic feasibility.